Toleransi Antar Agama (Studi Pada Siswa di SMPN 09 Mataram) - Ramadhani, Suci Yati; Ismail, M.; Alqadri, Bagdawansyah; Zubair, Muh. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of interfaith tolerance in students, supporting and inhibiting factors for the creation of interfaith tolerance in students, and. The research design used is a qualitative research design. The subjects in this study were 4 students, there were informants who were used as reinforcement. The researcher took informants from the Deputy Head of Student Affairs, PPKn Teacher, Hindu Religion Teacher, Islamic Religion Teacher purposively. The data collection techniques used were observation, interviews and documentation. The results of the study showed that, 1) interfaith tolerance in SMPN 09 Mataram has been implemented well through five main indicators, namely: recognizing everyone's religious rights, respecting the religious beliefs of others, agreeing on differences, understanding each other, and awareness and honesty. Students are given the freedom to practice their religion according to their beliefs, respecting religious activities between students, and making diversity a means to strengthen togetherness.2) supporting factors for the creation of inter-religious tolerance at SMPN 09 Mataram, namely: students' willingness to accept differences, the availability of adequate religious facilities and infrastructure, and cooperation between educators who create various inter-religious activities. 3) inhibiting factors for the creation of inter-religious tolerance in students, namely personal factors including students' lack of understanding of the meaning of tolerance, Family environmental factors, lack of encouragement and understanding of parents regarding the importance of tolerance, and community environmental factors, fanaticism and lack of appreciation for religious differences also form intolerant attitudes in students.